FACTORS INFLUENCING CONSUMERS’ PERCEPTION TOWARDS MOBILE PAYMENT USAGE IN MALAYSIA - Roseli, Nur Hazwani Mohamad; Azhar, Nurul Huda Najihah; Sauid, Muna Kameelah; Hasan, Zuhairah; Othman, Yuhanza (International Journal of Small and Medium Enterprises, 2021)
The advancement of smartphone technologies has led to many promising services such as payment through mobile or smartphone itself. In Malaysia, mobile payment usage is still low because consumers prefer to make payment transactions using other devices like laptops, computers, and credit card machines. Even though the adoption is still low but it shows an increasing trend. The purpose of this paper is to find factors influencing consumers’ perceptions of mobile payment usage. This study proposes three factors which are ease of use, trust, and security for the measurement. This quantitative study employed convenience sampling as the sampling technique and a total of 259 consumers as the respondents. All three factors were found could influence the consumers’ perception of mobile payment usage. Since this study is only limited to only three factors, there should be other factors to be included in future studies such as perceived cost, perceived benefits, cashback, rewards and many more. The conduct of this study will be beneficial to both service providers as well as the businesses using the services for improving their business models and business strategies.